Susceptibility and severity of COVID-19 and risk of psychiatric disorders in European populations: a Mendelian randomization study - Xue, Hua; Zeng, Li; Liu, Shuangjuan (Frontiers in Psychiatry, 2023)
Background: Observational studies have suggested that COVID-19 increases the prevalence of psychiatric disorders, but the results of such studies are inconsistent. This study aims to investigate the association between COVID-19 and the risk of psychiatric disorders using Mendelian randomization (MR) analysis.We used summary statistics from COVID-19 Host Genetics Initiative genome-wide association study (GWAS) of COVID-19 involving 2,586,691 participants from European ancestry. Genetic variations of five psychiatric disorders including autism spectrum disorder (ASD) (N = 46,351), bipolar disorder (BID) (N = 51,710), major depressive disorder (MDD) (N = 480,359), anxiety disorder (N = 83,566), and schizophrenia (SCZ) (N = 77,096) were extracted from several GWAS of European ancestry. The inverse-variance weighted (IVW) method as the main MR analysis conducted. We further performed sensitivity analyses and heterogeneity analyses as validation of primary MR results.The IVW analysis found that COVID-19 hospitalization phenotype was the risk factor for BID (OR = 1.320, 95% CI = 1.106-1.576, P = 0.002) and SCZ (OR = 1.096, 95% CI = 1.031-1.164, P = 0.002). Moreover, we detected a significant positive genetic correlation between COVID-19 severity and two psychiatric traits, BID (OR = 1.139, 95% CI = 1.033-1.256, P = 0.008) and SCZ (OR = 1.043, 95% CI = 1.005-1.082, P = 0.024). There was no evidence supporting the causal relationship between COVID-19 susceptibility and psychiatric disorders.Our results found that the COVID-19 hospitalization phenotype and COVID-19 severity phenotype might be the potential risks of BID and SCZ in European populations. Therefore, patients infected with SARS-CoV-2 should have enhanced monitoring of their mental status.